FASD a ASD. Podobieństwa i różnice - Buchnat , Marzena; Wojciechowska , Aneta (Studia Edukacyjne, 2024)
Fetal alcohol spectrum disorder (FASD) occurs in the population at about twice the rate of autism spectrum disorder (ASD). Various studies have discussed the association between the two disorders, but the results are nonconclusive. This article reviews the literature on the potential linkages between FASD and ASD in terms of symptoms, similarities and differences in behavior, and etiology. It also indicates the importance of an ASD diagnosis for children initially diagnosed with FASD.